Voluntary and involuntary childlessness : the joys of otherhood? - Sappleton, Natalie (Emerald Publishing Limited, 2018)
Childlessness is not a new phenomenon, but empirical evidence from the demographic field has demonstrated that it is on the increase. Furthermore, childlessness has a number of consequences for both women and men, the communities in which they live, their psychic states, their social networks and the organisations in which they work. Bringing together research from a wide range of scholarly disciplines, including philosophy, psychology, sociology, gender studies, social work and social policy, and underpinned by a feminist ontology this edited collection of original chapters provides an insight into the current state of the art research on the drivers, determinants, manifestations and outcomes of childlessness. The collection is intended to be a key resource for scholars, students and policymakers addressing this issue in a wide range of disciplinary contexts.
Includes index.
Keywords: Childlessness.; Parenting.; Family & Relationships / Parenting -- General.; Sociology: family & relationships.; elektronické knihy; electronic books